Genomic analysis of Vanessa tameamea, the threatened Hawaiian endemic butterfly, reveals population genetic structure relevant to conservation efforts - Haley E. Arnold; Julian R. Dupuis; Daniel Rubinoff; William P. Haines; Michael San Jose; Renee L. Corpuz; Angela N. Kauwe; Tyler J. Simmonds; Scott M. Geib; Sheina B. Sim (Conservation Genetics, 2025)
Patterns of divergence and speciation on islands have long been of interest in the broader study of evolution. Hawaiʻi’s endemic Kamehameha butterfly ( Vanessa tameamea ) is experiencing population decline, but because of its high vagility and assumed genetic homogeneity as a species, its population structure has not been investigated. To evaluate V. tameamea genetic variation across the Hawaiian Islands, we assembled a reference quality genome assembly for the species using HiFi and HiC reads and performed range-wide population genetic analyses using ddRAD sequencing data. A discriminant analysis of principal components (DAPC) revealed that, contrary to prior assumptions, V. tameamea populations appear to be diverging based on geography, in a pattern similar to other native Hawaiian terrestrial arthropods. Specifically, through demographic history analyses, we find that the distinct population on Kauaʻi is likely to be ancestral, the central islands of Maui, Molokaʻi, and Oʻahu comprise another population, and Hawaiʻi Island forms a third population, with likely more gene exchange with the central islands. Finally, we investigate the SNPs driving differences between groups and find that many are associated with genes that may be relevant to local adaptation to environmental chemicals such as host plant defenses or chemicals introduced by human activity, notably to do with metabolism and detoxification. While much field work remains to investigate any cryptic or phenotypic patterns as well as quantify effective migration, we hope that this work will inform refinement of conservation plans for one of Hawaiʻi’s two native butterflies.